Air monitoring with passive samplers for perfluoroalkane substances in developing countries (2017–2019). (November 2021) - Camoiras González, Pascal; Sadia, Mohammad; Baabish, Abeer; Sobhanei, Siamak; Fiedler, Heidelore
Abstract: To support the global monitoring plan on persistent organic pollutants (GMP) under the Stockholm Convention, 41 countries have exposed passive air samplers equipped with polyurethane foam disks (PUFs) to monitor perfluoroalkane substances (PFAS). The recommended procedure had PUFs exposed for three months during two years; analysis was performed in one expert laboratory to generate harmonized results. Chemical analysis using Soxhlet extraction with methanol or a 60:40 MTBE:methanol mixture, solid-phase extraction and UPLC/MSMS detection posed challenges as to matrix interference and sensitivity. Single PUFs as quarterly samples and combination of up to 4 PUFs as annual samples were analyzed; all concentrations were normalized to one PUF and 3 months exposure. Exceptionally high values (up to 36 000 pg SPFOS/PUF) were observed in nine samples from Zambia where a local source was identified. For the remaining 308 PUFs, PFOA had a higher median value (188 pg/PUF) than SPFOS (125 pg/PUF) whereas the mean value of SPFOS (254 pg/PUF) was slightly higher than the mean value for PFOA (230 pg/PUF). PFHxS concentrations were much lower in concentration and detection frequency and FOSA, as the only relevant PFOS precursor compound, showed a median value of zero. No clear regional differentiation was found. Graphical abstract: Image 1 Highlights: 350 polyurethane foam disks analyzed for PFOS and precursors, PFOA and PFHxS. PFOS (with wide range of values) and PFOA dominate over PFHxS and other PFAS. No correlation found between PFOS and its precursors. Low sorption capacity of PUFs hampers analysis and quantification of PFAS.